RESULTS OF STUDY OF THE NEW TOMATO VARIETIES IN ARMENIA - D. V. Khachatryan; S. A. Ayrapetova (Овощи России)
As a results of investigation, the new tomato varieties Eva, Narine, and an were selected for manufacturing application in different regions of Armenia. Cultivar Narine was registered in 2013. Cultivars Eva and Van are being tested for State Variety Trial.